Direct recovery of cyclodextringlycosyltransferase from Bacillus cereus using aqueous two-phase flotation - Lin, Y.K.; Show, P.L.; Yap, Y.J.; Tan, C.P.; Ng, E.P.; Ariff, A.B.; Annuar, M.S.M.; Ling, T.C. (2015)
Purification of cyclodextrin glycosyl transferase (CGTase) from Bacillus cereus using polyethylene glycol (PEG)-potassium phosphates aqueous two-phase flotation (ATPF) system was studied in this paper. The effects of varying PEG molecular weight, tie-line length (TLL) value, volume ratio (V-R), pH value, crude concentration and gas nitrogen flotation time were investigated. The optimal condition for purification of CGTase was attained at 18.0% (w/w) PEG 8000, 7.0% (w/w) potassium phosphates, V-R of 3.0, 20% (w/w) crude load at pH 7, and 80 min nitrogen flotation time at a flow rate of 5 L/min. With this optimal condition, purification factor (P-FT) of 21.8 and a yield (Y-T) of 97.1% were attained. CGTase was successfully purified in a single downstream processing step using the ATPF. (c) 2015, The Society for Biotechnology, Japan. All rights reserved.